Comparison of Undifferentiated Versus Chondrogenic Predifferentiated Mesenchymal Stem Cells Derived From Human Umbilical Cord Blood for Cartilage Repair in a Rat Model. Issue 2 (February 2019) - Park, Yong-Beom; Ha, Chul-Won; Kim, Jin-A; Kim, Seongchan; Park, Yong-Geun
Background: Human umbilical cord blood–derived mesenchymal stem cells (hUCB-MSCs) have gained much interest as a promising cell source for regenerative medicine owing to the noninvasive collection, availability, high expansion capacity, and low immunogenicity. However, few in vivo studies have reported the use of hUCB-MSCs on cartilage repair. Moreover, little study has been conducted on the effects of chondrogenic predifferentiation of hUCB-MSCs on cartilage repair. Purpose: To compare the effectiveness of transplanting undifferentiated versus chondrogenic predifferentiated mesenchymal stem cells (MSCs) for treating osteochondral defects. Study Design: Controlled laboratory study. Methods: Critical-sized osteochondral defects were created in the trochlear grooves of rat femurs. In 20 rats, a composite of chondrogenic predifferentiated hUCB-MSCs (chondro-MSCs) and 4% hyaluronic acid (HA) hydrogel was transplanted into defects in the right knees, whereas undifferentiated hUCB-MSCs (undiff-MSCs) and 4% HA hydrogel were transplanted into the left knees. In the control groups, 4% HA hydrogel without MSCs was transplanted into defects in the right knees, and the defects in the left knees were left untreated in 20 rats. The cartilage repair was evaluated at 8 and 16 weeks after surgery. Results: Transplanting undiff-MSCs resulted in overall superior cartilage repair as compared with chondro-MSCs, HA alone, or no treatment. The articular surfaces of the defect sites in the undiff-MSC group were relatively smoother than those of the other treatments. The undiff-MSC group showed cellular morphology and arrangement similar to surrounding normal articular cartilage tissue at 16 weeks, both of which were also better than those of the other groups. In addition, the undiff-MSC group showed coloration similar to surrounding normal articular cartilage tissue at 16 weeks in safranin O and type II collagen immunohistochemical staining. The histological scores also revealed that cartilage repair with undiff-MSCs was better than that with chondro-MSCs, HA alone, or no treatment ( P < .05 in all). Conclusion: This study demonstrated that treatment with undiff-MSCs resulted in more favorable cartilage repair than that with chondro-MSCs in a rat model. These findings indicate that chondrogenic predifferentiation of MSCs before transplantation does not enhance cartilage repair. Clinical Relevance: The results of this study support the use of undifferentiated MSCs, rather than chondrogenic predifferentiated MSCs, as a stem cell therapy strategy for cartilage repair.